DO THE VILLAGE FUND MANAGEMENT INFLUENCE ON THE ECONOMIC DEVELOPMENT OF THE VILLAGE? - Saiful Amin (JABE (Journal of Applied Business and Economic), 2020)
The village fund is one of the government policy programs that aims to ensure equitable development in Indonesia. This research aims to determine the influence of the village fund management on the economic development in Bondowoso district. It was performed to identify the relationship between the village fund management with village economic development. The method of this study using simple regression analysis. This results showed that coefficient determination of 0,291, means this model is able to explain the relationship between the independent variables with the dependent variable of 29,1%. While the rest is influenced by other variables not included in this research model. For hypothesis testing showed that the t value is 4.363 and the significant value in the results of this test is 0,000 less than 0.05. It can be concluded that village fund management has a significant effect on economic development of the villages in Bondowoso district.  Village funds that are managed in a transparent, accountable, participatory, and sustainable manner can increase village economic development.